Effectiveness of Bacillus nigr Liquid Organic Fertilizer on Early Growth Parameters of Coconut Plants - Lita Nasution; Desi Sri Pasca Sari Sembiring; Saipul Sihotang; Dedi Holden Simbolon (Yayasan Sinergi Multidimensi Kreatif, 2025)
The coconut palm (Cocos nucifera) is an economically and culturally significant crop widely cultivated in tropical regions, particularly in Indonesia. However, coconut productivity remains suboptimal due to aging plantations and poor soil conditions. To address this, biofertilizers such as Bacillus nigr have been proposed as sustainable alternatives to chemical fertilizers. This study aimed to evaluate the effect of Bacillus nigr-based liquid organic fertilizer (POC) on the early growth parameters of coconut plants aged 9 to 12 months. Conducted in Deli Serdang, North Sumatra, the experiment involved 38 coconut seedlings divided equally into treatment (POC) and control groups. Data on stem height were collected and analyzed using a T-test. The results demonstrated a statistically significant difference (p < 0.05) in stem height between the POC-treated and untreated plants, with notable growth advantages observed in the control group at 11 and 12 months. However, POC treatment showed promising effects at earlier growth stages (9–10 months). These findings suggest that Bacillus nigr-based POC may influence early vegetative growth, but long-term benefits and dosage optimization require further investigation. This study contributes to the growing body of knowledge on the role of microbial biofertilizers in sustainable coconut cultivation and offers insights for enhancing early-stage coconut growth using environmentally friendly agricultural practices.